La création d’emplois en Grande-Bretagne dans les années 1990 - Martine Azuelos (Revue Française de Civilisation Britannique)
Job creation in Britain in the 1990s has been either altogether ignored or else celebrated as evidence of the success of the reforms implemented since the early 1980s. But, so far, little work has been devoted to the study and interpretation of available data on the subject. This article first examines the size and pace of employment growth in the 1990s, setting these against the backdrop of longer term trends. It then focuses on the major sectoral shifts and changing profiles of jobs in contemporary Britain, and identifies various factors accounting for faster job growth.